(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2025)
The low level of critical thinking skills among students in physics education poses a major challenge in 21st-century education. This study aims to analyse the effectiveness of the guided inquiry model assisted by PhET simulations in enhancing students’ critical thinking skills on physics topics. The method used was a Systematic Literature Review (SLR) of eight articles published between 2020 and 2024, obtained through a Google Scholar search and selected based on inclusion and exclusion criteria using the PRISMA protocol. Each article was analysed based on the research method, the physics topic, the evaluation format, and N-gain scores for improvements in students’ critical thinking skills. The results of the study indicate that the guided inquiry model assisted by PhET is consistently effective in improving critical thinking skills, with N-gain scores ranging from 0.56 to 0.72 (moderate to high category). PhET simulations aid in visualising abstract concepts through interactive virtual experiments, while guided inquiry encourages structured scientific investigation by students. The integration of both contributes significantly to creating meaningful, active, and exploration-based learning. This study provides a conceptual and practical foundation for physics teachers in designing inquiry-based learning strategies supported by simulation technology to optimally develop students’ critical thinking skills.